Implementasi Program Rehabilitasi Ekosistem Mangrove di Kecamatan Tugu Kota Semarang - Debby Rinata Abadi; Ari Subowo; Aufarul Marom (Journal of Public Policy and Management Review, 2014)
The Program of Rehabilitation Mangrove Ecosystem Tugu Sub – District, Semarang City is due to by the high levels of abrasion that occurs in coastal areas and has an impact on society who live there. Therefore, the Department of Marine and Fisheries of Semarang City try to repair the condition of coastal areas by doing Rehabilitation Mangrove Ecosystem. This policy based on Law No.32/2009, Regulation of Semarang District No.7/2010, and  Regulation of Semarang District No.14/2011. The purpose of this study is investigate the process implementation and the factors that affect its. The purpose can be achieved if the process implementation following the Riant Nugroho’s criteria that is the accuracy of the policy, the accuracy of the implementation, the accuracy of target, the accuracy of environment and the accuracy of process. The implementation of Rehabilitation Mangrove Ecosystem influenced of supporting and inhibiting factors. Based on the theory of George C. Edwards III that supporting and inhibiting factors such as communication, bureaucratic structure, resources and attitudes.The results of this study show that the Department of Marine and Fisheries of Semarang City having ready for the implementation of Rehabilitation Mangrove Ecosystem. However, the implementation of Rehabilitation Mangrove Ecosystem is not well implemented.. There are several factors such as (1) the limitation financial resources and implementer official (2) the unavailability of technical guidelines (SOP) for the implementation and (3) the lack of monitoring for ecosystem that has been rehabilitated (4) the utilization KKMKS forum is minimal.